A special judo fitness test as an indicator of the differences in anaerobic capacity of judoists of various ages - Milosevic, N.; Atanaskovic, A.; Lolic, D. (Sports Science and Health, 2012)
The research was carried out on a sample of 24 elite judoists from the Kinezis club, aged 15 to 18, with a body weight of 66kg ± 15.50. All of the participants were subjected to an identical research protocol. The participants were divided into two age categories (cadets 12, juniors 12). The aim of the research was to determine the differences in anaerobic capacity between the aforementioned groups. In order to evaluate the anaerobic capacities of judoists, a special judo fitness test was used. The use of a t-test did not determine any differences between the cadets and juniors, which might be ascribed to the identical training program and similar sports careers of the tested judoists.